(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The article analyzes the economic geographical factors affecting the development of the infrastructure of the educational system. The infrastructure of the educational system, in turn, consists of a number of elements such as educational buildings, technological resources, pedagogical personnel, financial resources and transport systems, and economic conditions and geographical location are of great importance for its effective operation. have The article examines the impact of the level of economic development, investments and financial resources on the education system. It also analyzes how geographic factors such as differences between urban and rural areas, regional economic conditions, and population density determine the effectiveness of educational infrastructure